Sharing Autism Through Metaphors. (Dis)ability, Difference and Diversity in Temple Grandin’s Portrayals of Autism. - Marion Schmidt (Current Objectives of Postgraduate American Studies)
Autistic people, professionals claim, lack the socio-emotional awareness to employ metaphors. Yet public, medical and neuroscientific discourse about autism is full of metaphors, including those used by autistic people themselves. Analyzing the autobiographic writings of Temple Grandin – livestock scientist and autism spokeswoman – I treat her metaphors as shared sociocultural resource negotiating the identities of autistic people within a larger context of changing American disability narratives and identity politics.